Dental fear, tobacco use and alcohol use among university students in Finland: a national survey - Pohjola, Vesa (BioMed Central, 2014)
BACKGROUND: Tobacco- and alcohol use are associated with psychological problems. Individuals with high dental fear also more often report other psychological problems than do those with lower level of dental fear. We evaluated the association between dental fear and tobacco- and alcohol use while controlling for age, gender, general mood and feelings in social situations. METHODS: The data (n = 8514) were collected from all universities in Finland with an electronic inquiry sent to all first-year university students. Dental fear was measured with the question: “How afraid are you of visiting a dentist?” with reply alternatives “Not at all”, “Somewhat” and “Very”. Regularity of tobacco use was determined with the question: “Do you smoke or use snuff?”, with reply alternatives “Not at all”, “Occasionally” and “Daily”. The Alcohol Use Disorders Identification Test (AUDIT) was used for determination of alcohol use; an AUDIT sum score of 8 or more indicated hazardous, harmful or dependent alcohol use. The statistical tests used were Chi-square tests and Multiple logistic regression analyses. RESULTS: When controlled for age, gender, alcohol use, general mood and feelings in social situations, those who used tobacco regularly were more likely to have high dental fear than were those who used tobacco occasionally or not at all. When controlled for age, gender, general mood and feelings in social situations, those with hazardous, harmful or dependent alcohol use were more likely to have high dental fear than were those with low-risk of alcohol use, the association between alcohol use and dental fear was not strong. When tobacco use was added into this model, alcohol use was no longer statistically significantly associated with dental fear. CONCLUSIONS: The findings of this study support the suggestion that some people may have common vulnerability factors linked to tobacco use, alcohol use, and dental fear.